2011
DOI: 10.1007/978-3-642-23786-7_46
|View full text |Cite
|
Sign up to set email alerts
|

Value Ordering for Finding All Solutions: Interactions with Adaptive Variable Ordering

Abstract: Abstract. We consider the impact of value ordering heuristics on the search effort required to find all solutions, or proving none exist, to a constraint satisfaction problem in k-way branching search. We show that when the variable ordering heuristic is adaptive, the order in which the values are assigned to variables can make a significant difference in all measures of search effort. We study in depth an open issue regarding the relative merit of traditional value heuristics, and their complements, when sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Cardiac pathology was determined in 28 patients (5.91%) on readmission on one-month follow-ups of the patients who were recorded to have a non-cardiac pathology on the first admission. On the first admission, the mean MPV values were determined as 7.54 95% CI (7,76), and the mean platelet values were determined as 230060 95% CI (210000-285000). When the patient group that was determined to have cardiac pathology on re-admission was compared with the (MACE -) patient group, the MPV level was statistically significantly higher (p=0.039).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac pathology was determined in 28 patients (5.91%) on readmission on one-month follow-ups of the patients who were recorded to have a non-cardiac pathology on the first admission. On the first admission, the mean MPV values were determined as 7.54 95% CI (7,76), and the mean platelet values were determined as 230060 95% CI (210000-285000). When the patient group that was determined to have cardiac pathology on re-admission was compared with the (MACE -) patient group, the MPV level was statistically significantly higher (p=0.039).…”
Section: Resultsmentioning
confidence: 99%
“…ACS is among the first leading fatal causes of chest pain and it should be promptly and accurately managed by the clinicians. Troponin is used as a cardiac marker when electrocardiogram (ECG) is not diagnostic however, easy and fast cost-effective additional laboratory tests are required as this laboratory test takes a long time, has a low diagnostic value within the first 12 hours, and yields negative results in 14-20% of the patients (7). Apart from the cardiac markers, the platelet count and MPV measurement are the most studied parameters for the clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…On inconsistent subproblems, the order in which we select values in a domain has little effect because we must try them all. Recently, Mehta et al [2011] have shown that value ordering could have an effect when using an adaptive variable ordering heuristic. As adaptive variable ordering heuristics are affected by past operations of the search procedure, selecting a value instead of another can have an effect on the next choice of variable.…”
Section: Value Orderingmentioning
confidence: 99%